How Do Immigrants Promote Exports? Networks, Knowledge, Diversity. - Gianluca Orefice; Hillel Rapoport; Gianluca Santoni (Institute of Labor Economics (IZA), 2022)
How do immigrants promote exports? To answer this question we propose a unified empirical framework allowing to identify and disentangle the main mechanisms put forth in the literature: the role of networks in reducing bilateral transaction costs, and the productivity shifts arising from migrationinduced knowledge diffusion and increased workforce diversity. While we find evidence supporting all three channels (at both the intensive and the extensive margins of trade), our framework allows to gauge their relative importance. When focusing on diversity, we find stronger results in sectors characterized by more complex production processes and more intense teamwork cooperation. This is consistent with theories linking the distribution of skills to the comparative advantage of nations. The results are robust to using a theoretically-grounded IV approach combining three variations on the shift-share methodology.
Keywords: F14; F16; F22; O47; 330; international trade; birthplace diversity; migration; productivity